QANDLI DIABET KASALLIGINING PSIXOLOGIK JIHATDAN TADQIQ QILIINISHI - Sadikova, U.B. (SCIENCE and SOCIETY, 2022)
The article analyzes the relevance of the psychological study of diabetes, the importance of research in its study, psychological intervention in medicine, a number of studies on the psychological application of patients with diabetes in foreign countries.
Keywords: diabetes mellitus; psychological aspects of the disease; insulin; metabolic disorders; emotional state; experience